Pengaruh Latihan Push-Up Terhadap Peningkatan Kekuatan Otot Lengan pada Siswa Ekstrakurikuler Bola Voli di SMPK Nurobo - Dixon Taek Bete (Universitas Persatuan Guru 1945 NTT, 2020)
Based on the observations I have made at SMPK Nurobo, there were some grade VIII students who did not master volleyball techniques, such as top service, which tends to be dominated by male students of grade VIII. This happened because the exercised was focused only to the lower service. The purpose of this study is: to determine the extent of the effect of push-up exercises to increase the arm muscle strength in volleyball extracurricular activity for the students at SMPK Nurobo. The method in this research is a quantitative research which is the experimental method, namely One Group Pre-Post Test Design. The data collection technique used is the treatment and documentation test, while the data analysis technique used is the Similar Sample T-Test. The results of the data analysis shown that the average pre test of the arm muscle strength was 11.5, the average of the final test was 12.4 and t-count = 8.99. The results of the next calculation are compared with df: N-1 (10-1), in the t-table at a significant level of 5%, we get a t-count of 8.99> t table 1.833 (5%). Thus the Alternative Hypothesis (Ha) which was stated that: